2021
DOI: 10.3390/genes12071050
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Ovarian and Other Cancers Risks by Population and BRCA Mutation Location

Abstract: Hereditary breast and ovarian cancer is caused by a germline mutation in BRCA1 or BRCA2 genes. The frequency of germline BRCA1/2 gene mutation carriers and the ratio of germline BRCA1 to BRCA2 mutations in BRCA-related cancer patients vary depending on the population. Genotype and phenotype correlations have been reported in BRCA mutant families, however, the correlations are rarely used for individual risk assessment and management. BRCA genetic testing has become a companion diagnostic for PARP inhibitors, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 89 publications
(120 reference statements)
3
25
0
Order By: Relevance
“…Regarding the difference in OC risk depending on the BRCA mutation location, BRCA1 and BRCA2 have the ovarian cancer cluster region (OCCR) in or near exon 11 and the breast cancer cluster region (BCCR) in multiple regions other than exon 11 so far [ 9 10 11 ]. However, there are few reports on the correlation between BRCA mutation location and age at diagnosis of OC.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the difference in OC risk depending on the BRCA mutation location, BRCA1 and BRCA2 have the ovarian cancer cluster region (OCCR) in or near exon 11 and the breast cancer cluster region (BCCR) in multiple regions other than exon 11 so far [ 9 10 11 ]. However, there are few reports on the correlation between BRCA mutation location and age at diagnosis of OC.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of histological subtypes is known to be different between Japan and Western countries; the rate of clear cell carcinoma is higher in Japan (approximately 25%) than in the United States (approximately 6%), a four-fold difference [ 19 , 20 ]. The prevalence of g BRCA1/2 -PV in HGSC and clear cell carcinoma in OC is also reported as higher and lower, respectively, in Japan than in Western countries [ 21 , 22 ]. Therefore, the total prevalence of g BRCA1/2 -PV in all OC cases may be similar between Japan and Western countries despite the difference in the frequency of histologic subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of factors have been associated with its incidence, several of which are genetic. Indeed, approximately 40% of inherited cancers are due to mutations in the breast cancer susceptibility genes 1 and 2 ( BRCA1 and BRCA2 ) [ 2 ]. Recent estimates have shown that approximately 70% of patients with mutations in BRCA1 and 45% in BRCA2 will develop BC by the age of 70 [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%